Pterygodermatites (Nematoda: Rictulariidae) : revisão de literatura e identificação de espécies em quirópteros da Mata Atlântica, sudeste brasileiro - Simões, Mariana Brandão (2016)
Nematodes of the genus PterygodermatitesWedl, 1861encompass 38 described species distributed throughoutthe globe, except in the Australian region. These nematodes have structures that are hard to visualize and to identify, hamperingtaxonomic works on the group. The first chapter is based on a theoretical reference about the group, emphasizinga historical survey ofthe genusin order to understand the classification criteria that led them to the currenttaxonomic position, as well as the characters used in splitting the genusintofive subgenera. This chapter also depicts the biologicalcycle of the parasite and host-parasite relationships, giventhe potentialfor hostswitching. The second chapter reflects a field research conducted on rodents, marsupials,and bats collected in the Atlantic Forestof eastern Brazil, to find the parasitic nematodes Pterygodermatites,identify them and select the best characters forthe taxonomic work. Pterygodermatites wasfound only in bats and we identifiedtwo species already recorded in southeastern Brazil: Pterygodermatites(Paucipectines) elegans(Travassos, 1928) and Pterygodermatites(Paucipectines) jagerskioldi(Lent & Freitas, 1935), the latterhad only been reported in marsupals. Furthermore, wedescribed a potentially new species belonging to the subgenus Pterygodermatites, which was only known from Europe, Asia and CentralAmerica, expanding the knowngeographical distribution of the group. In this second chapter, we also discussedthe main diagnostic characters and the selection of some structures that have not been used in the taxonomy of the group. Wealso provide anidentification keyfor the genus, as well as a comparative table with diagnosticstructures that are not necessarily present in the taxonomic key,but willfacilitate taxonomic identification. In addition, this paper provides the expansion of the morphological and taxonomic characterization of the genus, contributing for the enhancement about knowledge in evolutionary and ecological aspects of the group.